Non-Adherence To Antihypertensive Treatment in Essential Hypertensive Patients in Rajshahi, Bangladesh - Hussanin, SM; Boonshuyar, C; Ekram, ARMS (Anwer Khan Modern Medical College Journal, 2011)
A total of 120 hypertensive patients were recruited from two sites: Rajshahi Medical College Hospital (RMCH) and a private clinic in Rajshahi. Eighty five percent of this study population were non-adherent to treatment. The clients of RMCH were more non-adherent. Additional factors determining non-adherence included: lower level of educations, low family income, duration of diagnosis, knowledge and belief of the disease, lack of accompanying person to go to the physician/hospital, and deficiencies in information from the service provider. Since hypertension is a chronic disease, patients should be encouraged to take their medication regularly and follow the lifestyle advised. Collective participation by all allied health personnel should be encouraged. Community based studies should be conducted to discover the extent of non-adherence to antihypertensive treatment. Key words: Non-Adherence; Hypertension; Antihypertensive; Belief; Knowledge DOI: 10.3329/akmmcj.v2i1.7465 Anwer Khan Modern Medical College Journal 2011; 2(1): 09-14